A review of ion adsorption clay as a high potential source of rare earth minerals in Malaysia - Nurul Anniyah, Sobri; Mohd Yusri, Mohd Yunus; Noorlisa, Harun (Elsevier Ltd, 2023)
Rare earth elements (REEs) have emerged as a critical component in manufacturing various products for green technology. This paper aims to comprehensively review the formation of ion adsorption clay, REEs weathering profile, clay minerals’ potential in adsorbing REEs, ion-exchange mechanism and method for REEs extraction, and the potential of ion adsorption clay as a REEs source in Malaysia. In conclusion, ion adsorption clay has significant potential as a REEs mineral source in Malaysia, where a higher concentration of REEs has been identified compared to China, a developing country in the REEs minerals industry of ion adsorption clay.